Wybrane aspekty polityki kredytowej przedsiębiorstw wobec kontrahentów - Czarecki, Jacek (Selected Aspects of Companies Credit Policy Towards Their Clients, 2008)
The term of payment policy for clients is the part of liquidity management. One of the most important aspects of this policy is shaping invoice maturity. This paper is an attempt to show positive features of implementing factoring instruments in prolongation of invoice maturities. The article presents how the surveyed entrepreneurs who use factoring have benefited from prolonging maturities. The research was carried out by the author on the basis of analysis of 43 companies. The research conclusions have confirmed that factoring is a good financing instrument that provides opportunity of prolonging invoice maturity.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 18, s. 19-27